PIXE, Particel Induced X-ray Emission a concise review - (:unkn) unknown (My University, 1998)
PIXE-Particle Induced X-Ray Emission is a multielemental, sensitive and non-destructive method which has been in use in trace elemental analysis since 1970. This review aims to explain the main features of PIXE. References will be given at the end for those that seek more detailed knowledge on the principles and applications of this technique.
Keywords: Elemental analysis; Ion induced X-ray; Particle induced X-ray emission; Trace element